Virgin microplastics cause toxicity and modulate the impacts of phenanthrene on biomarker responses in African catfish (Clarias gariepinus) - Karami, Ali; Romano, Nicholas Paul; Galloway, Tamara; Hamzah, Hazilawati (Elsevier, 2016)
Despite the ubiquity of microplastics (MPs) in aquatic environments and their proven ability to carry a wide variety of chemicals, very little is known about the impacts of virgin or contaminant-loaded MPs on organisms. The primary aim of this study was to investigate the impacts of virgin or phenanthrene (Phe)-loaded low-density polyethylene (LDPE) fragments on a suite of biomarker responses in juvenile African catfish (Clarias gariepinus). Virgin LDPE (50 or 500µg/L) were preloaded with one of two nominal Phe concentrations (10 or 100µg/L) and were exposed to the fish for 96h. Our findings showed one or both Phe treatments significantly increased the degree of tissue change (DTC) in the liver while decreased the transcription levels of forkhead box L2 (foxl2) and tryptophan hydroxylase2 (tph2) in the brain of C. gariepinus. Exposure to either levels of virgin MPs increased the DTC in the liver and plasma albumin: globulin ratio while decreased the transcription levels of tph2. Moreover, MPs modulated (interacted with) the impact of Phe on the DTC in the gill, plasma concentrations of cholesterol, high-density lipoprotein (HDL), total protein (TP), albumin, and globulin, and the transcription levels of fushi tarazu-factor 1 (ftz-f1), gonadotropin-releasing hormone (GnRH), 11 β-hydroxysteroid dehydrogenase type 2 (11β-hsd2), and liver glycogen stores. Results of this study highlight the ability of virgin LDPE fragments to cause toxicity and to modulate the adverse impacts of Phe in C. gariepinus. Due to the wide distribution of MPs and other classes of contaminants in aquatic environments, further studies are urgently needed to elucidate the toxicity of virgin or contaminant-loaded MPs on organisms.